Avaliação da topografia corneana e correlação com a intensidade da dermatocálase antes e após blefaroplastia superior - Frantz, kariza Aiko (2013)
The purpose was to determine, using Orbscan examination, if dermatochalasis can lead to changes in corneal topography and to correlate any changes in corneal topography after blepharoplasty with the intensity of dermatochalasis. We analyzed 46 eyes from 23 patients without eyelid or corneal pathologies. We obtained measurements of the distance between the upper eyelid margin and upper eyelid crease (margin-crease distance) through digital images. Orbscan examinations were performed before and after upper blepharoplasty. The patients' age ranged from 41 to 64 years, with 01 (4.3%) male and 22 (96.7%) females. There was no statistically significant difference between the topographic parameters analyzed before and after upper blepharoplasty. Also there was no correlation between the margin-crease distance in millimeters and the difference of astigmatism after blepharoplasty. We conclude that dermatochalasis, in this study, did not lead to changes in corneal topography. The corneal astigmatism did not change significantly after upper blepharoplasty.